Hemophilus Influenzae Vaccine and Guillain-Barre - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
A four-year-old girl with Guillain-Barre syndrome that developed 10 days following H influenzae type b conjugate vaccine immunization is reported from Geneva, Switzerland.